Technologies creation analysis of constructive materials of high on tension constructive mmaterials - Матченко, Т.І.; Рожновська, О.С. (Proceedings of National Aviation University (archive), 2004)
The analysis of technological procenes of constructive metalcompositives with the given high strength meaning, rigidity and the given low dimity meaminys of thermal expansion was done.